2009
DOI: 10.1063/1.3116582
|View full text |Cite
|
Sign up to set email alerts
|

Probing chiral solute-water hydrogen bonding networks by chirality transfer effects: A vibrational circular dichroism study of glycidol in water

Abstract: Vibrational absorption (VA) and vibrational circular dichroism (VCD) spectra of (S)-(-)-glycidol were measured in water with a concentration of 6.0M in the 1000-1750 cm(-1) region. Prominent and complex VCD spectral features were detected at the water bending vibrational region. Our experimental results show that water molecules can become optically active through hydrogen bonding interactions with glycidol molecules. To model the glycidol-water hydrogen bonding network in the solution, molecular dynamics simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 64 publications
3
58
0
Order By: Relevance
“…Although challenging, quantum chemical predictions for clusters, or solute–DMSO complexes, are to be considered when DMSO solvent is used for experimental measurements. The same comment applies for other hydrogen bonding solvents as well, and studies on solute–solvent clusters are becoming more common in recent years . A recent review by Tomasi and coworkers can be consulted for further insights on modeling the solvent influence.…”
Section: Resultsmentioning
confidence: 96%
“…Although challenging, quantum chemical predictions for clusters, or solute–DMSO complexes, are to be considered when DMSO solvent is used for experimental measurements. The same comment applies for other hydrogen bonding solvents as well, and studies on solute–solvent clusters are becoming more common in recent years . A recent review by Tomasi and coworkers can be consulted for further insights on modeling the solvent influence.…”
Section: Resultsmentioning
confidence: 96%
“…For some of the low-intensity modes even larger intensity changes can be found. Previous studies 34 showed that for measurements in a CHCl 3 solution the use of solvation models was found to yield Phys. Chem.…”
Section: Discussionmentioning
confidence: 98%
“…One main goal is to illustrate that VCD and ROA, especially induced solvent VCD features, offer the unique opportunity to differentiate water molecules which form long‐lived direct contacts with the chiral solute from those in the bulk water environment. For example, the induced water VCD signatures at the water bending vibrational region were observed experimentally,,,, and such induced chirality VCD features are due exclusively to the water molecules which are part of the chiral solute‐water n complexes. A second goal is to evaluate the utility of the recently proposed “ clusters‐in‐a‐liquid ” solvation model .…”
Section: Introductionmentioning
confidence: 94%